Real‐Time Non‐Faradaic Potentiodynamic Impedance Sensing Using Screen‐Printed Carbon Electrodes - Fuhry, Emil (2024)
Electrochemical impedance spectroscopy (EIS) is a suitable analytical technique to detectinterfacial phenomena and analyte binding at electrode surfaces. In contrast to metallicelectrodes, carbon-based electrodes are more suited due to the low cost and the availability ofmore versatile methods for chemical functionalization. For (bio) sensing, often the Faradaicversion of EIS in a three-electrode configuration is used, where a redox-active species is usedas a marker. In order to avoid interference due to the redox-active marker with the interfacialinteraction, we focus here on the use of non-Faradaic EIS in the absence of any added markers.First, we utilize the sedimentation of silica beads as a model system, which reduces thecomplexity of the interaction simplifying the interpretation of the measured signals. Moreover,we introduce two improvements. First, impedance measurements are performed in a threeelectrodeconfiguration with applied potential as an additional variable, which serves as ahandle to optimize the sensitivity. Secondly, we present a time-differential strategy to detectsubtle changes and demonstrate that we can consistently follow the sedimentation of beadsusing the non-Faradaic impedance as a function of the applied potential. Finally, we show aproof-of-principle demonstration for the biosensing of cell attachment on the electrodes in realtimeusing the proposed technique.